Informatycznie wspomaganie rachunkowości budżetowej i zarządzania finansami jednostek oświatowych sektora publicznego - Borowiec, Leszek (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The company’s information system, has a special impact because of both, their qualities and cognitive flexibility to include the object of measurement and observation. Development of accounting associated with the need to assist management procedures. The purpose of this study was to show information budgetary accounting role by presenting software supporting of accounting and financial management of public sector enterprises using in the District Office of Education Finances Warszawa Śródmieście to support and service educational units. There was made the analysis utility and scope of the use of Vulcan software, which specializes in providing applications for accounting services public sector educational institutions.